A non-local perturbation of the logistic equation in IRN. (October 2019) - Delgado, M.; Molina-Becerra, M.; Santos Júnior, J.R.; Suárez, A.
Abstract: A logistic equation in the whole space is considered. In this problem, a non-local perturbation is included. We establish a new sub–supersolution method for general nonlocal elliptic equations and, consequently, we obtain the existence of positive solutions of a nonlocal logistic equation.